2016
DOI: 10.1111/brv.12279
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural synchronization of large‐scale animal movements – disperse alone, but migrate together?

Abstract: Dispersal and migration are superficially similar large-scale movements, but which appear to differ in terms of inter-individual behavioural synchronization. Seasonal migration is a striking example of coordinated behaviour, enabling animal populations to track spatio-temporal variation in ecological conditions. By contrast, for dispersal, while social context may influence an individual's emigration and settlement decisions, transience is believed to be mostly a solitary behaviour. Here, we review differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 267 publications
1
59
0
Order By: Relevance
“…Parent–offspring and sib–sib analyses typically yield higher heritability estimates than Animal Models (McCleery et al, ; Charmantier et al, ; Doligez et al, ), due to maternal and common environment effects (van Noordwijk et al, ; Zera & Brisson, ). Further, heritability estimates may also be inflated by biases in detectability due to limited study areas (van Noordwijk, ; Doligez & Pärt, ) and to more numerous social interactions among siblings synchronizing their movements (Matthysen, Van de Casteele & Adriaensen, ; Cote et al, ). As a whole, heritability studies suggest that variation in dispersal can arise as a result of additive genetic variation, but also that in many cases much of the phenotypic variation is explained by environmental variation, including transgenerational effects (Appendix I).…”
Section: Empirical Evidence For the Genetic Basis Of Dispersalmentioning
confidence: 99%
See 2 more Smart Citations
“…Parent–offspring and sib–sib analyses typically yield higher heritability estimates than Animal Models (McCleery et al, ; Charmantier et al, ; Doligez et al, ), due to maternal and common environment effects (van Noordwijk et al, ; Zera & Brisson, ). Further, heritability estimates may also be inflated by biases in detectability due to limited study areas (van Noordwijk, ; Doligez & Pärt, ) and to more numerous social interactions among siblings synchronizing their movements (Matthysen, Van de Casteele & Adriaensen, ; Cote et al, ). As a whole, heritability studies suggest that variation in dispersal can arise as a result of additive genetic variation, but also that in many cases much of the phenotypic variation is explained by environmental variation, including transgenerational effects (Appendix I).…”
Section: Empirical Evidence For the Genetic Basis Of Dispersalmentioning
confidence: 99%
“…In fact, both the evolution of increased or decreased dispersal can be predicted for species expanding over fragmented landscapes or experiencing a sudden fragmentation event (Leimar & Norberg, ; Heino & Hanski, ; Gyllenberg, Parvinen & Dieckmann, ; Travis, Smith & Ranwala, ; Poethke, Gros & Hovestadt, ; Cote et al, ). On the one hand, as habitat fragmentation imposes diverse costs during transfer (Bonte et al, ; Baguette & Van Dyck, ), we can simply expect a reduction in dispersal propensity (reviewed in Cote et al, ). In the bog fritillary butterfly Boloria ( Proclossiana ) eunomia , dispersal propensity was dramatically decreased by landscape fragmentation, which induced higher dispersal mortality (Schtickzelle, Mennechez & Baguette, ; Schtickzelle et al, ).…”
Section: Empirical Evidence For the Genetic Basis Of Dispersalmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings of reduced hybridization rates observed when the rare species is clustered can be viewed as a beneficial effect of group dispersal (García & Grivet ; Cote et al . ), since this mechanism results in aggregated patterns of related dispersers. Here, we have shown that this provides a local pollen pool biased towards more conspecific pollen, resulting in increased protection against hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…Goodnight, ; Gardner & West, ), a behaviour also observed in other social species such as in bacteria ( Myxococcus xanthus ; Velicer & Yuen‐Tsu, ) and banded mongooses ( Mungos mungo ; Cant et al ., ; Nichols et al ., ). This empirical evidence suggests an alternative evolutionary path to the emergence of cooperation, in which cooperation is mediated by the budding mode of dispersal, and yet this problem has received surprisingly little attention (for a review, see Cote et al ., ). Specifically, how different ecological and demographic factors, such as environmental stability and the cost of dispersal, influence the evolution of budding dispersal and cooperation remains unexplored.…”
Section: Introductionmentioning
confidence: 99%